BANK COMPETITION AND RISK TAKING: EMPIRICAL EVIDENCE FROM VIETNAMESE BANKING INDUSTRY - LA, THI KIM KHANH (2018)
This dissertation studies the level of bank competition, risk taking behaviour and their nexus in Vietnam. Based on a data set of commercial banks from 2011 to 2017, the results suggest a decrease in competition proxied by Lerner Index over the period and hint a slight increase in banks’ risk taking estimated by Z-score. The dissertation agrees with the “competition-stability” hypothesis and shows evidence supporting the “too-big-to-fail” theory, as larger banks tend to take more risks in this market. Moreover, the empirical results in Vietnam indicate a deviation from Structure-Conduct-Performance hypothesis and non-structural indicator appears to be better in reflecting market power than the structural one. Foreign ownership, still limited by the government, does not make significant changes on the stability. Meanwhile, state-controlled banks are supposed to stabilise the banking system with a low level of market power. Overall, this dissertation provides important implications for bank restructuring, competition and regulatory framework in Vietnam.